پاکستانی معاشرت میں مہنگائی کے بڑھتے مسائل اور ہماری ذمہ داریاں: قرآن وسنت کے سماجی اصولوں کی روشنی میں تجزیاتی مطالعہ: Rising Inflation Problems in Pakistani Society and Our Responsibilities: An Analytical Study in the Light of Social Principles of Quran and Sunnah - Dr. Hafiz Faiz Rasool; Dr. Muhammad Azam; Mehwish Kiran (International Research Journal of Arabic and Islamic Studies, 2024)
The trend of rising inflation has become a major concern in Pakistani society, affecting every segment of the population. As the cost of goods continues to rise, the economic pressure on households, businesses and the overall economy intensifies. The purpose of this study is to explore the complex dynamics of inflation in Pakistan, examining its causes and consequences through an analytical lens. Furthermore, it seeks to reconcile these economic challenges with the social principles outlined in the Qur'an and Sunnah, which emphasize the moral responsibilities of individuals, businesses, and government. Understanding and solving these problems is very important for establishing a fair and balanced society. Inflation has been a persistent problem in Pakistan, affecting the socio-economic fabric of the country. Historically, Pakistan has experienced varying inflation rates, with significant increases during periods of political instability, global economic changes, and adverse domestic policies. Over the past few decades, inflation has increased due to a number of factors, including fluctuating oil prices, rising import costs, and unbalanced agricultural production. The impact of inflation is felt deeply at all social levels, but it disproportionately affects low- and middle-income households, increasing poverty and reducing purchasing power. This economic stress has been exacerbated by issues like currency devaluation and widening fiscal deficit. In light of these challenges, it is important to implement the social principles enunciated in the Qur'an and Sunnah, which emphasize justice, fairness, and social welfare. Islamic teachings advocate fair trade, prohibiting exploitative practices, and helping the needy, providing an ethical framework for dealing with economic problems. By integrating these principles, a more equitable economic system can be developed that not only curbs inflation but also promotes social harmony and well-being. This article sheds light on the current trends in inflation in Pakistan, with the aim of reconciling economic solutions with the ethical guidelines provided by Islamic teachings.